The Screening Test Interfacial Tension of Palm Based Surfactant for Enhanced Oil Recovery (EOR) Application - Gadi, Agatha Maria; Hambali, Erliza; Permadi, Pudji (Proceeding of Chemistry Conference; Vol 2 (2017): 11th Joint Conference on Chemistry 2016, 2017)
Sodium Methyl Ester Sulfonate (SMES) surfactant is one type of anionic surfactant which has advantages in terms of detergency, hardness, renewable and environment-friendly. Excess surfactant SMES could be utilized in the process of oil displacement through EOR technology (Enhanced Oil Recovery / Tertiary Recovery) which is a technology that involves the injection of a material that can cause changes in fluid properties and reservoir rocks such as oil composition, temperature, ratio mobility and characteristics rock-fluid interactions. The use of SMES Surfactant is intended to determine the value of interfacial tension (IFT) between oil-water so as to lift the oil to come out of the pores of reservoir rocks. The EOR surfactant must meet one of the testing parameter screening is the IFT measurement. The surfactant formulation determining by optimum range concentration from 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% and 1% of SMEs w/w dissolved with formation water or water injection by heating to 50 °C solution temperature is reached. The best screening results contained at a concentration of 0.3% with a IFT value <10 -3 dyne / cm.